1988
DOI: 10.1007/bf01952199
|View full text |Cite
|
Sign up to set email alerts
|

Platelet research in psychiatry

Abstract: The platelet is one of the most researched biological markers in psychiatry. Characteristics of MAO activity, 5-HT uptake, imipramine and alpha 2-adrenergic receptor binding, for example, are similar in platelet and CNS. Methodological factors are not negligible, and range from diagnostic specificity and drug effects to the normal physiological variability of age and hormone-related changes, circadian and seasonal rhythms. As yet, there are no clear state or trait platelet markers in affective disorders and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 105 publications
1
23
0
1
Order By: Relevance
“…Still, platelets are traditionally used as a peripheral model for neurons and have been shown to reflect brain insults in several neuropsychiatric disorders. 21,22 For example, parallel alterations in brain and platelets were found in imipramine binding of depressed patients and patients who committed suicide, 23 and in complexes I and IV activities in patients with Parkinson's and Alzheimer's diseases, respectively. 24,25 Furthermore, mitochondria have an additional advantage, since they are partly independent organelles containing their own DNA, and their respiratory system is highly preserved along evolution and in different tissues.…”
mentioning
confidence: 99%
“…Still, platelets are traditionally used as a peripheral model for neurons and have been shown to reflect brain insults in several neuropsychiatric disorders. 21,22 For example, parallel alterations in brain and platelets were found in imipramine binding of depressed patients and patients who committed suicide, 23 and in complexes I and IV activities in patients with Parkinson's and Alzheimer's diseases, respectively. 24,25 Furthermore, mitochondria have an additional advantage, since they are partly independent organelles containing their own DNA, and their respiratory system is highly preserved along evolution and in different tissues.…”
mentioning
confidence: 99%
“…In addition, alterations in platelet SERT have been observed in many psychiatric disorders and vascular diseases in which 5-HT has been implicated (Meltzer et al, 1981). Therefore, platelets have been widely used as a peripheral indicator of central 5-HT metabolism and SERT function (Wirz-Justice, 1988).Based on a previous study using human embryonic kidney (HEK-293) cells stably transfected with human SERT (hSERT), we reported that activation of PKC and/or inhibi- …”
mentioning
confidence: 99%
“…A significant reduction in neuronal membrane viscosity should thus lead to a commensurate reduction of serotonin. This would explain similarities between neurons and platelets in major depression (Takahashi, 1976;Edwards, 1978;Marangos, 1979;Kim, 1982;Rotman, 1983;Dreux, 1985;Wirz-Justice, 1988;Camacho, 2000;Plein, 2001;MaurerSpurej, 2007).…”
Section: Quantitative and Quantum Approaches To Psychopathologymentioning
confidence: 99%